Bioethics and assisted death: freedom to die? - Cunha, Amanda Maria Silva da (2021)
The objective of this work is to gather elements that allow reflecting on the ethical dilemma about assisted death, considering the principle of preserving life and the freedom to die promoted by human's autonomy in the decision on finitude. It is a reflection study carried out in three steps: the search for literature that addressed the theme, the rescue of cases from the authors' experience that inspired fictional situations demonstrating the dilemma, the writing of texts that presented the issue and promoted dialogue. It is shown that the issue has become extremely complex, involving themes such as death technologies, transhumanist discourse and the care of terminally ill patients, raising bioethical, philosophical and political issues, indicating that freedom to die is related to acceptance of death as a natural and unambiguous stage of the life cycle and the power that the human has over itself in its own process of death.